Identification of interneurons activated at different inclines during treadmill locomotion in adult rats. Issue 12 (27th June 2014) - Tillakaratne, Niranjala J.K.; Duru, Paul; Fujino, Hidemi; Zhong, Hui; Xiao, Mei Si; Edgerton, V. Reggie; Roy, Roland R.
<x xml:space="preserve">Abstract</x> By using c‐fos as an activity‐dependent marker, we identified the cholinergic interneurons around the central canal and lumbar interneurons throughout the gray matter that were activated after a 30‐min bout of quadrupedal treadmill stepping at a 0° or 25° incline in adult rats. Increased loading (elevated treadmill incline) imposed during treadmill stepping activated more cholinergic interneurons in the proximity of the central canal, i.e., central canal cluster cells and partition neurons. Since cholinergic central canal cells are thought to modulate motoneuron excitability, these data suggest that increased load during stepping may increase motoneuronal activity through activating more cholinergic central canal cells. We identified the muscle‐specific motoneurons and afferent terminals in the spinal cord by injecting cholera toxin subunit B in the soleus and tibialis anterior muscles. The number of interneurons in lumbar segments L4 (tibialis anterior) and L5 (soleus) was higher in both groups that stepped on the treadmill compared with control and was highest in rats that stepped at a 25° incline. In a majority of laminae, the distribution of total and muscle‐specific activated interneurons was highest in the 25° incline group and lowest in the control group for both muscles. These data could reflect increased peripheral (proprioceptive) input as well as supraspinal drive associated with stepping and demonstrate the differences in 1) the activation of cholinergic interneurons near the central canal and 2) the laminar and segmental location of interneurons throughout the gray matter that play a role in generating stepping under different loading conditions in adult rats. © 2014 Wiley Periodicals, Inc.